The Legality of the Supervision Model in the Police Academy Education System - Budi Susanto; Nur Qudus; Widiyanto Widiyanto; Rodiyah Rodiyah (Lex Scientia Law Review, 2026)
The Police Academy plays a strategic role in shaping Indonesian National Police officers with integrity, professionalism, and a strong Bhayangkara character. One of the principal instruments in this process is the cadet supervision system implemented within a residential education setting. In practice, the supervision model often encounters legal issues, particularly regarding the legal basis of authority, the limits of responsibility, and compatibility with the national education legal framework and the internal regulations of the Indonesian National Police. The analysis examines the legality of the supervision model within the Police Academy education system and assesses its conformity with applicable laws and regulations. A normative juridical method is employed, using statutory and conceptual approaches. The findings indicate that the supervision model achieves legal legitimacy when positioned as an integral component of official service education management, integrated with character education, and supported by clear internal regulations. Strengthening the legal foundation of the supervision system is essential to ensure legal certainty, human rights protection, and accountability in the administration of police education. The analysis confirms that a legally grounded supervision model is a fundamental prerequisite for the formation of faithful police officers who possess integrity and demonstrate professionalism.